Conveyor Model with Input and Output Accumulating Bunker - Pihnastyi, O. M.; Kozhevnikov, G. K.; Khodusov, V. D. (Institute of Electrical and Electronics Engineers, Inc., USA, 2020)
In this article, a model of a conveyor-type transport system with an input and output bunker is developed. The transport conveyor is presented in the form of a dynamic distributed system. It is shown that the material flow is proportional to the linear density of material distribution along the transport route. The coefficient of proportionality is the speed of the belt. When constructing the model, the assumption of the absence of oscillatory processes associated with the tension of the conveyor belt is introduced, which corresponds to the case when the function determining the speed of the belt is only a function of time. A solution is given, that determines the state of the flow parameters of the conveyor section for a given point of the transport route at an arbitrary point in time. It is shown that the state of the flow parameters for an arbitrary place in the transport route is determined by the state of the flow parameters at the input of the conveyor section, considering the transport delay. An expression is written that allows to calculate the amount of transport delay. The relationship of the transport delay value with the algorithm for controlling the conveyor belt speed is demonstrated. A system of equations for the model of a conveyor-type transport system with an input and output bunker is obtained. The behavior of the model for several characteristic cases of the functioning of the transport system is analyzed. The constructed model of the control object can be used to design highly efficient control systems for the flow parameters of the transport system with an input and an output bunker.
Keywords: production line; optimal control; distributed system; transport system